1999
DOI: 10.1161/01.cir.99.23.3071
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiomyocyte Apoptosis and Changes in Proapoptotic and Antiapoptotic Genes bax and bcl -2 During Left Ventricular Adaptations to Chronic Pressure Overload in the Rat

Abstract: These data suggest that in response to chronic pressure overload, cardiomyocyte-specific apoptosis contributed to the transition from LVH to LVD. LVH and LVD were accompanied by a dramatic cardiomyocyte upregulation of the proapoptotic gene bax and reduced bcl-2/bax ratio, predisposing cardiomyocytes to apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
182
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(199 citation statements)
references
References 19 publications
14
182
2
1
Order By: Relevance
“…Ikeda et al (17) reported no change in the expression of either Bax or Bcl2 proteins between the stages of hypertrophy and failure in spontaneously hypertensive rats. Induction of Bax, but not Bcl2, was observed during the transition to left ventricular dysfunction during chronic pressure overload in rats (11). Our study in 9-month-old Tg mice overexpressing myotrophin showed a significant increase in both the pro-apoptotic gene Bax, as well as the anti-apoptotic gene Bcl2, at both RNA and protein levels during transition from hypertrophy to heart failure.…”
Section: Figmentioning
confidence: 43%
“…Ikeda et al (17) reported no change in the expression of either Bax or Bcl2 proteins between the stages of hypertrophy and failure in spontaneously hypertensive rats. Induction of Bax, but not Bcl2, was observed during the transition to left ventricular dysfunction during chronic pressure overload in rats (11). Our study in 9-month-old Tg mice overexpressing myotrophin showed a significant increase in both the pro-apoptotic gene Bax, as well as the anti-apoptotic gene Bcl2, at both RNA and protein levels during transition from hypertrophy to heart failure.…”
Section: Figmentioning
confidence: 43%
“…The Bcl-2 gene suppresses apoptosis induced by many other factors (17) and the Bax gene encodes a 21-kDa protein, and has 21% homology with the Bcl-2 gene (18). Overexpression of the Bax gene inhibits the function of Bcl-2 and promotes apoptosis (19).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, BAX expression increases and BCL2 expression decreases during chronic experimental cardiac pressure overloading (Condorelli et al, 1999), NIX/BNIP3L is upregulated in human and experimental cardiac hypertrophy (Yussman et al, 2002;Galvez et al, 2006), and BNIP3 expression increases in ischemic cardiac models (Regula et al, 2002;Galvez et al, 2006). Recent data support a particularly important function for BNIP3 and NIX/BNIP3L in cardiomyocyte apoptosis during ventricular remodeling.…”
Section: Cardiomyocyte Apoptosis and Bcl2 Proteins In Myocardial Diseasementioning
confidence: 94%